2021
DOI: 10.1002/er.6818
|View full text |Cite
|
Sign up to set email alerts
|

Metal hydrides for thermochemical energy storage applications

Abstract: Due to the depletion of natural energy resources, worldwide, solar energy is accepted as an emerging energy source because it is free, endless and can be convertible to other forms, but it is intermittent. Therefore, in the present study, different energy storage techniques, that is, sensible heat, latent heat and thermochemical heat storage techniques, suitable to store solar thermal energy are discussed and compared. Based on the energy storage density, reaction kinetics, operating temperature range and volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Metal hydrides (MHs) have been used in several thermal applications such as cooling, heating, hydrogen compression, and so on, discussed in review articles. [13][14][15][16] Review articles based on MH-based TES applications have focused majorly on Mg-based metal alloys. Some of them also reviewed low-temperature MHs (LTMHs) such as alanates and borohydrides.…”
Section: Review Statusmentioning
confidence: 99%
“…Metal hydrides (MHs) have been used in several thermal applications such as cooling, heating, hydrogen compression, and so on, discussed in review articles. [13][14][15][16] Review articles based on MH-based TES applications have focused majorly on Mg-based metal alloys. Some of them also reviewed low-temperature MHs (LTMHs) such as alanates and borohydrides.…”
Section: Review Statusmentioning
confidence: 99%
“…This charged material releases heat during the discharging process, enabling applications such as water heating, space heating, and power generation. Thermochemical materials (TCMs) like salt hydrates [33,34], metal hydroxides [35,36], carbonates, zeolites [37,38], metal organic frameworks [39], metal oxides [40], metal hydrides [41][42][43][44] and composites [45,46] exhibit diverse reactions. TCMs offer a significantly higher energy storage density, approximately 8 to 10 times greater than sensible energy storage and twice that of phase change materials (PCMs) [47].…”
Section: Thermochemical Energy Storage (Tces)mentioning
confidence: 99%
“…Apart from this, the selection of alloy also depends on its thermodynamic properties (i.e., reaction enthalpy and entropy), operating temperatures, and pressures. It is also observed that many studies have been carried out on single-stage TCESs, including the authors' previous studies, [3,7,21] in which several metal hydride pairs were tested to identify their suitability for TCES at different operating conditions. Though many studies are available on single-stage TCESs, the study can be extended further for multistaging to achieve higher efficiency.…”
Section: Introductionmentioning
confidence: 99%